Cytoprotective effect of deferiprone against aluminum chloride-induced oxidative stress and apoptosis in lymphocytes. (15th March 2018) - Zhuang, Cuicui; She, Yue; Zhang, Haiyang; Song, Miao; Han, Yanfei; Li, Yanfei; Zhu, Yanzhu
Highlights: Aluminum trichloride (AlCl3 ) induces oxidative stress and change antioxidant enzyme activities in lymphocytes. Deferiprone (DFP) attenuates AlCl3 -induced oxidative stress and apoptosis in lymphocytes. Cytoprotective effect of deferiprone against aluminum chloride-induced immunosuppression. Abstract: Aluminum (Al) is a toxic metal, and excessive Al accumulation causes immunosuppression. Deferiprone (DFP) is a well-known chelator and used in dialysis patients for removing Al from tissues. The present study aimed to investigate whether DFP treatment can attenuate immunotoxicity induced by aluminum chloride (AlCl3 ) in cultured lymphocytes. Lymphocytes were treated with 0 and 0.6 mmol/L AlCl3 ∙6H2 O (pH 7.2) and/or 1.8 mmol/L DFP, respectively. Immune function of lymphocytes was assessed by T and B lymphocytes proliferation rates, T lymphocyte subpopulations and IL-2, IL-6 and TNF-α contents. In addition, lymphocyte damage was assessed by LDH activity, NO and MDA contents, NOS, SOD and GSH-Px activities, lymphocyte apoptosis index. These results showed that AlCl3 exposure reduced T and B lymphocyte proliferation rates, CD3 + and CD4 + T lymphocyte subpopulations, CD4 + /CD8 + ratio, IL-2, IL-6 and TNF-α contents, SOD and GSH-Px activities, early and later lymphocyte apoptosis indexes while enhanced CD8 + T lymphocyte subpopulation, NO and MDA contents, LDH activity. DFP treatment attenuated the immunotoxicity of lymphocytes and reduced oxidative stress and lymphocyte apoptosis induced by AlCl3, indicating that DFP could protect lymphocytes against immunosuppression induced by AlCl3 through attenuating oxidative stress and apoptosis.